2018
DOI: 10.1016/j.cossms.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Current developments of nanoscale insight into corrosion protection by passive oxide films

Abstract: Oxide passive films are a key for the durability of metals and alloys components as well as a central issue in corrosion science and engineering. Herein, we discuss current developments of the nanometer and sub-nanometer scale knowledge of the barrier properties and adsorption properties of passive oxide films brought by recent model experimental and theoretical investigations. The discussed aspects include (i) the chromium enrichment and its homogeneity at the nanoscale in passive films formed on Cr-bearing a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 119 publications
1
43
0
6
Order By: Relevance
“…As suggested by recent nanometer scale studies [27,48], the Cr(III) enrichment may not be homogeneous in the passive film, and the Cr enrichment heterogeneities may cause the local failure of the passivity and the initiation of localized corrosion followed by pit growth where the passive film fails to self-repair [49]. The better understanding of the mechanisms governing the Cr (and Mo) enrichment requires to thoroughly investigate the initial stages of oxidation leading to pre-passivation of the SS surface [50,51,52] as well as the alterations brought by electrochemical passivation of the native oxide-covered SS surface [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by recent nanometer scale studies [27,48], the Cr(III) enrichment may not be homogeneous in the passive film, and the Cr enrichment heterogeneities may cause the local failure of the passivity and the initiation of localized corrosion followed by pit growth where the passive film fails to self-repair [49]. The better understanding of the mechanisms governing the Cr (and Mo) enrichment requires to thoroughly investigate the initial stages of oxidation leading to pre-passivation of the SS surface [50,51,52] as well as the alterations brought by electrochemical passivation of the native oxide-covered SS surface [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…It is now well-established from surface analytical studies of passivity performed on ferritic and austenitic SS at macroscopic level that the key for efficient passivity is a marked Cr(III) enrichment of the passive film, because of the higher stability of Cr(III) compared to Fe(II,III) oxide/hydroxide species [1][2][3][4][5][6][7][8]. For austenitic SS, only very little Ni(II) is present when detected in the passive film and the metallic alloy region underneath the oxide is Ni(0)-enriched [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This corrosion resistance comes from the passive film which is a surface oxide film only a few nanometers thick and strongly enriched in Cr(III) (hydr)oxide species. [1][2][3][4][5][6][7] Even though numerous studies have characterized the passivity of various SS grades at macroscopic level, only recent surface analytical works performed on austenitic SS have suggested that the origin of passivity breakdown, which can lead to the local failure of the corrosion resistance and to localized corrosion by pitting, would depend on the surface heterogeneity at microscopic level. [6][7][8] Hence, the distribution of the chromium enrichment in the passive film at the nanometric scale appears of paramount importance for the stability and barrier properties of the passive film and its resistance to localized corrosion initiation.…”
Section: Introductionmentioning
confidence: 99%